A survey of the UPHSI Students ptc-lasting ability and their lifestyle. - Antiquiera, Marianne Feliz (UPHSI, 2015)
Phenylthiocarbamide (PTC) is a bitter chemical compound that can divide humans into two groups: the tasters and the non-tasters. Non-tasters tend to eat more bitter foods that result to higher body weight that leads to obesity. This study aimed to determine the PTC-tasting ability of UPHSI students' and compare their lifestyles. This study also compared the body mass index (BMI) of students and determined whether there is a significant correlation between their ability to taste PTC with their lifestyle. The reliability test of the questionnaires was conducted at Iloilo National High School - School of the Future last December 11, 2014. The final survey was conducted last January 27, 2015 at the UP High School classrooms. The collection of anthropometric data was conducted last January 28, 2015 to February 6, 2015. The strips were evaluated by the UPV-CAS Ethics Review Board and the tasting test was conducted last February 6, 2015 at the UP High School Building. The data collected were then encoded in preparation for analysis. The number of students who took the reliability test was determined using Cochran's formula and were selected using random sampling. The data gathered will be interpreted by the researchers using inferential statistics and statistical tools such as mean, median, mode, standard deviation, Spearman Rho, and Mann-Whitney Test. The results showed that 84.3% of the students are tasters and 15.7% are non-tasters. There is no significant difference in the sleeping pattern and diet between tasters and non-tasters. Non-tasters do more sedentary activities and 42.9% of them belong to either overweight or obese category for body mass index. There is no significant correlation between PTC-tasting ability with sleeping pattern and diet but it has a significant correlation to physical activities specifically, running/jogging, walking, and jumping rope.